Analysis of ways of improvement of the diamond lapidary enterprise financial system - D. A. Shutov (Путеводитель предпринимателя)
The analysis of methods of improving the financial system of diamond lapidary enterprise has been done, as well as the matrix definition ofthe type ofsystem ofbudgeting has been proposed.